Eksistensi Program Kampus Mengajar Angkatan 4 dalam Meningkatkan Literasi dan Numerasi di SDN Karang Nangkah 1 - Meithia Fani; Didiek Tranggono (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
The Teaching Campus Program is one of the Free Learning-Free Campus (MBKM) programs formed by the Ministry of Education and Culture (Kemendikbud) on February 9 2021. The Teaching Campus contributes to the world of education at the elementary (elementary school) and junior high school (junior high school) levels ) which is located in the 4T region (Foremost, Outermost, Disadvantaged, and Transmigration areas) and an accredited school under A. SDN Karang Nangkah 1 is one of the targets of the 4th batch teaching campus program in improving literacy and numeracy, assisting administration, and technology adaptation. Service activities are the result of collaborative research using descriptive qualitative as a scientific method often used and carried out by a group of researchers in the field of social sciences, including education. Data collection through observation (observation), in-depth interviews (in-depth interviews), and documentation. Through the campus teaching program students can collaborate and contribute by having a positive impact on students and the school. The campus teaching program activities include; mentoring teaching and learning activities, library management, one day one book, socialization of literacy movement, IT training, and implementation of AKM Class. From the implementation of the program, it is hoped that it will provide benefits in overcoming problems based on the needs of schools, teachers and students in literacy and numeracy skills, technology adaptation, and administrative assistance at SDN Karang Nangkah 1. In addition, students in the teaching campus program can develop capacity knowledge, expertise according to their competence and able to develop education in Indonesia optimally.